2023
DOI: 10.26554/sti.2023.8.1.32-37
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Characteristics of Edible Film Using Modified Cassava Starch Over Ethanol Precipitation

Abstract: Cassava starch has been widely explored as film forming material, however its hydrophilicity restricts its application. Hydrophobic material such as modified starch can be used in the film elaboration to improve its quality. This study aims to examine the effect of modified cassava starch concentration on the physical, barrier, and mechanical properties of edible films. A completely randomized design was used with 5 concentrations of modified starch at 0%, 5%, 10%, 15%, and 20% and 4 repetitions to obtain a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In related tests, a consecutive augmentation of nano starch at concentrations ranging from 0.5% to 10% notably enhanced the thickness of water chestnut starch films (Dularia et al, 2019). Similar research findings regarding mung bean starch films and modified casava starch films were reported by Roy et al (2020) and Pratama et al (2023), demonstrating that the inclusion of nano starch at different concentrations led to an increased thickness of the resulting nanocomposite film, respectively. This phenomenon could be attributed to amylose chain degradation during acid hydrolysis, resulting in condensation reactions that scaled proportionally with the quantity of nano starch incorporated into the film (Kim et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In related tests, a consecutive augmentation of nano starch at concentrations ranging from 0.5% to 10% notably enhanced the thickness of water chestnut starch films (Dularia et al, 2019). Similar research findings regarding mung bean starch films and modified casava starch films were reported by Roy et al (2020) and Pratama et al (2023), demonstrating that the inclusion of nano starch at different concentrations led to an increased thickness of the resulting nanocomposite film, respectively. This phenomenon could be attributed to amylose chain degradation during acid hydrolysis, resulting in condensation reactions that scaled proportionally with the quantity of nano starch incorporated into the film (Kim et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the results demonstrate that the addition of starch nanoparticles led to a decrease in the solubility of the composite film. Similar results were observed by Jiang et al (2016) and Pratama et al (2023) in their study on pea starch films filled with potato starch nanoparticles, and modified casava starch films, while Sharma et al (2021) reported that the solubility of kidney bean starch nanocomposite films increased with an increasing concentration of nano starch.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the relative degree of crystallinity is pivotal as it influences the physical and chemical properties of the nanoparticles. The extent of crystallinity affects the nanoparticles’ thermal stability, mechanical strength, and interaction with surrounding environments [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%